Taxonomic notes on the genus Epidaus Stål (Heteroptera: Reduviidae: Harpactorinae) from Vietnam, with the description of a new species - Truong, Xuan Lam; Zhao, Ping; Cai, Wanzhi (Zootaxa, 2006)
Four species of Epidaus Stål from Vietnam are recognized and keyed. Epidaus sexspinus Hsiao and Epidaus longispinus Hsiao are reported for the first time from Vietnam. Epidaus bachmaensis Truong, Zhao & Cai, sp. nov. is described and its dorsal habitus, head, pronotum, male genitalia, and other diagnostic morphological features are illustrated.